(untitled) (Rudarsko-geološko-naftni zbornik, 2015)
Geological structure of the terrain as a ground for a battlefield could be a significant factor for the success or failure of a military operation. The geology of the Belgian town of Ypres was an important, maybe even crucial factor, of the failure of the WWI Allied Powers offensive military operations against German Axis forces in 1917. The Early Eocene clays found at the ground surface at Ypres, coupled with excess precipitation, turned out to be utterly inappropriate for the fortification, movement, fighting and manoeuvring of all military units, especially the armoured units that were directed towards hardly passable routes. With selecting the unsuitable and hardly passable terrain, that is the direction of the attack, the British army had losses of the available combat potential and armoured forces were ineffective during the battle. The total number of Allied casualties was 448,000 dead, wounded, imprisoned and missing. This paper offers other possible solutions that would, from a military geographic and military geological viewpoint, have made a better solution for achieving the strategic goal required by the Allies on the eve of the Third Battle of Ypres in 1917.